PENGARUH KUALITAS PRODUK DAN PENETAPAN HARGA TERHADAP MINAT BELI PADA ANEKA KUE ANANDA SIAK - Prastika Wulandari; Lie Othman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Buying interest is one of the most important factors in the marketing concept, this is what lies behind this research. Good product quality, setting the right price is the most important part of the factors supporting buying interest. This study aims to determinane the effect of product quality, pricing on buying interest in Aneka Kue Ananda Siak, to determine and the effect of product quality on buying interest in Aneka Kue Ananda Siak, to determine the effect of pricing on buying interest in Aneka Kue Ananda Siak and to determine the effect of product quality and pricing on buying interest in Aneka Kue Ananda Siak. The research location is in Aneka Kue Ananda Siak on jalan Dr. Soetomo, Kampung Dalam Village, Siak District, Siak Regency. The reaserch sample was 100 respondents with accidental sampling technique. The reaserch method used in this study is descriptive and quantitative, with data sources from primary dan secondary data. The analytical method used in this study in simple linear regression analysis and multiple linear regression, and through validity and reliability tests. In this study the results obtained are the Product Quality (X1) has an effect on Buying Interest (Y), Pricing (X2) has an effect on Buying Interest (Y), and Product Quality (X1) and Pricing (X2) has an effect on Buying Interest (Y) on Aneka Kue Ananda Siak Keyword : Product Quality, Pricing, Buying Interet